Associations of metabolic syndrome in SLE. Issue 1 (13th November 2020) - Apostolopoulos, Diane; Vincent, Fabien; Hoi, Alberta; Morand, Eric
Abstract : Objectives: To characterise the prevalence and associations of metabolic syndrome (MetS) in a multiethnic cohort of patients with SLE. Methods: Using a standardised protocol, baseline demographics, per visit disease activity (Systemic Lupus Erythematosus Disease Activity Index-2K) and treatment data, and annual recording of organ damage accrual (Systemic Lupus International Collaborating Clinics/American College of Rheumatology (SLICC-ACR) Damage Index) were captured on patients with SLE from a single tertiary centre. The presence of MetS, defined using modified updated joint consensus criteria, was assessed at the final visit from patient records. Serum concentrations of adipocytokines were measured by Quantibody. Results: 116 patients, with median (Q1, Q3) age at enrolment of 39.5 (31.4–51.1) years and disease duration of 6.1 (1.4–12) years, were followed for a median of 6.7 (4.1–8.1) years. The prevalence of MetS was 29% (34/116), while the prevalence of MetS components varied: hypertension (59%), low high-density lipoproteins (HDLs) (51%), hypertriglyceridaemia (32%), obesity (16%) and hyperglycaemia (22%). In univariable analysis, MetS was associated with baseline organ damage (OR 4.34; 95% CI 1.80 to 10.48; p<0.01) and organ damage accrual (OR 2.34; 95% CI 1.02 to 5.36; p=0.04) but not with disease activity. In multivariable analysis, baseline organ damage remained significantly associated with MetS (adjusted OR 3.36; 95% CI 1.32 to 8.59; p=0.01). Glucocorticoid use was not associated with MetS or any of its five components. High serum concentrations of resistin were significantly negatively associated with MetS (OR 0.17; 95% CI 0.04 to 0.70; p=0.014). Conclusion: MetS was common in a multiethnic cohort of patients with SLE, with the most frequent components being hypertension and low HDL. An independent association was found between MetS and organ damage but not glucocorticoid exposure or disease activity.